Understanding Customer Needs and Preferences in Head-mounted Display Virtual Reality Experiences - Kim, K. (South African Journal of Industrial Engineering, 2025)
This study investigated consumer perceptions of head-mounted display-based virtual reality systems, focusing on factors influencing adoption, usage, and purchase decisions. Using a survey of 112 participants, the research examined the technological, psychological, and economic considerations shaping user experiences. Factor analysis identified six critical dimensions: usefulness, usability, capabilities, content and system satisfaction, engagement, and risk. Regression analyses revealed that engagement is the primary driver of purchase intention, while usefulness predominantly influences usage intentions and future adoption perspectives. Content and system satisfaction emerged as an additional determinant across both adoption and purchase behaviours. Despite positive perceptions of immersion, realism, and originality, users expressed concerns about content quality and cost. These findings underscore the need to enhance engagement and usefulness, alongside improving content and system satisfaction, to foster a broader acceptance and integration of head-mounted display virtual reality technologies. Limitations in the survey’s regional focus are acknowledged, suggesting the need for cross-cultural studies. This research offers actionable insights for the developers and stakeholders of head-mounted display virtual reality systems, contributing to the advancement and popularisation of VR systems.